2018
DOI: 10.1093/tbm/iby112
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivors’ preferences for social support features in technology-supported physical activity interventions: findings from a mixed methods evaluation

Abstract: Incorporating peer and professional social support features into remotely delivered, technology-supported physical activity interventions may increase their effectiveness. However, very little is known about survivors’ preferences for potential social features. This study explored breast cancer survivors’ preferences for both traditional (e.g., coaching calls and peer support) and innovative (i.e., message boards and competitions) social support features within remotely delivered, technology-supported physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Some techniques, such as social support, commonly included in trials for weight management had wide ranges of perceived importance, bringing down the mean rating in our small sample. This could be because social support features can take many shapes in mHealth interventions (eg, Facebook group, coaching calls, and message boards), which have varying levels of appeal . Future research should further explore which types of social support are most valued by breast cancer survivors from underserved populations.…”
Section: Discussionmentioning
confidence: 99%
“…Some techniques, such as social support, commonly included in trials for weight management had wide ranges of perceived importance, bringing down the mean rating in our small sample. This could be because social support features can take many shapes in mHealth interventions (eg, Facebook group, coaching calls, and message boards), which have varying levels of appeal . Future research should further explore which types of social support are most valued by breast cancer survivors from underserved populations.…”
Section: Discussionmentioning
confidence: 99%
“…Adding peer support features to technology-based exercise interventions may enhance their effectiveness [ 42 ] and may be appealing to younger cancer survivors [ 7 , 43 , 44 ]. A mixed methods study of breast cancer survivors’ preferences for social support features within technology-supported, remotely delivered physical activity interventions revealed that survivors were highly interested in using technology-supported message boards to post questions, give and receive feedback, and share ideas with other survivors [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adding peer support features to technology-based exercise interventions may enhance their effectiveness [ 42 ] and may be appealing to younger cancer survivors [ 7 , 43 , 44 ]. A mixed methods study of breast cancer survivors’ preferences for social support features within technology-supported, remotely delivered physical activity interventions revealed that survivors were highly interested in using technology-supported message boards to post questions, give and receive feedback, and share ideas with other survivors [ 42 ]. Similarly, survivors believed that sharing their exercise on a progress board or within a private community would help formalize goals, create a sense of accountability, and facilitate an understanding of their achievements relative to their peers [ 42 ]—behavioral theory–supported behavior change techniques [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations